Effect of footwear interventions on muscle discomfort and lower leg muscle fatigue among industrial workers - Omar, Noreen Adila (2021)
Introduction: Prolonged standing has been recognized as one of the factors which contributes about83% of MSDs among industrial workers (Zander, King and Ezenwa, 2004). Many ergonomics interventions have been recommended to reduce the effects of prolonged standing andvibration massage was found as an effective solution to delayed onset of muscle pain and discomfort. Objective: Thus, main objective of this study was to study the effect of prototype insole built-in massager on lower leg muscle discomfort among industrial workers during prolonged standing. Methodology: The study was conducted in a controlled room at a selected manufacturing company in Selangor which involved 110 male respondents. First phase of study involved the identification of characteristics in Product Design Specification (PDS) for an ideal prototype insole built-in massager. Then, second phase involved the experimental study design in which the prototype insole built-in massager being compared with other interventions (footrest and anti-fatigue mat) and control group (normalshoe). The respondents evaluated their discomfort rating using Borg’s Scales Questionnaire for every 15 minutes. At the same time, sEMG electrodes were attachedDuring the 2-hours standing, all respondents would do a task which were sorting the mixed items at the workstation provided. Results and discussion: Results indicated that respondents do experience mild discomfort on all their body parts during the experimental study especially at the lower body parts. Interventions (prototype insole built-in massager, footrest and anti-fatigue mat) groups had showed reductions in discomfort rating for all body parts compared to control group.The sEMG results indicated that prototype insole built-in massager gave the lowest percentage of exertion (22.38 – 42.2%) for all muscles studied compared to other interventions (anti-fatigue mat and footrest). There was a positive effect of discomfort level on both left and right Tibialis anterior and Gastrocnemius with the usage of prototype insole built-in massager compared to control group.There was a significant difference of discomfort rating between control and prototype insole built-in massager shoe group at ankle and feet, knee and calf part(p<0.05).Besides, there were significant differences of means for sEMG level (p<0.001) of the prototype built-in massager with other interventions (anti-fatigue mat and footrest). Conclusion and recommendations: Overall, there were positive indicator that the prototype insole built-in massager reduced the muscle discomfort of lower leg muscles to the workers compared to other interventions.Vibration massager in the insoles increase the blood circulation by relaxing foot muscles and decrease the discomfort level of the feet. However, this study recommended a much bigger population and more variation in measurement was needed. This prototype insole built-in massager can also serve as the reference required for the future interventions of prolonged standing among industrial workers.